Penerapan Metode Hazard and Operability Study (HAZOP) Pada Analisis Keselamatan dan Kesehatan Kerja di PT Asia Pacific Fibers TBJ., Performance Fabrics - Kolondam, Grace Monica Arlenne; Nugraha, Asep Erik (Peneliti.net, 2024)
Preventing work accidents within the company is closely related to efforts to maintain employee welfare and carry out social and legal responsibilities. Work accidents not only have the potential to threaten individual safety and health, but can also impact the company's productivity and reputation. In collecting and processing this data, two methods were applied, namely interviews and direct observation. Interviews were used to determine the variables that would be used in the research, with the aim of understanding the concerns and obstacles experienced by machine operators. Direct observations are carried out to evaluate field conditions related to occupational safety and health, ensure compliance with standards, and to identify potential risks of work accidents. Consequences (level of injury severity) and likelihood (possible level of risk of work accidents occurring), and then the results obtained are three (3) sources of danger which are classified as extreme, fifteen (15) sources of danger which are classified as high and two (2) sources of danger that are classified as moderate. It is necessary to instill awareness of the importance of Occupational Safety and Health (K3) in the workplace to reduce the risk of work accidents and make workers safe and comfortable in carrying out their duties. This awareness cultivation is not only applied to machine operators, but to all elements within PT. Asia Pacific Fibers Tbk, Performance Fabrics.